2018
DOI: 10.1371/journal.pone.0192381
|View full text |Cite
|
Sign up to set email alerts
|

Five year outcomes of Boston type I keratoprosthesis as primary versus secondary penetrating corneal procedure in a matched case control study

Abstract: Despite improved retention and reduced complication rates paving the way for the current expansion of applications and surge in prevalence for the Boston type I Keratoprosthesis (KPro), the most frequent indication for its implantation today remains prior graft failure. The purpose of this study is to evaluate the long-term outcomes of primary KPro and compare to secondary implantation in a matched cohort study. This study included patients who underwent KPro implantation in a single center by two surgeons bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…An alternative option is a Boston keratoprosthesis, however, it is an invasive procedure, which changes the eye anatomy and physiology drastically and irreversibly [34, 35]. Despite the improvements in visual function, there are frequent risks of ocular complications, such as glaucoma development and progression of pre-existing glaucoma [36, 37]. Hence, vigorous peri-operative management and long-term follow-up are required .…”
Section: Discussionmentioning
confidence: 99%
“…An alternative option is a Boston keratoprosthesis, however, it is an invasive procedure, which changes the eye anatomy and physiology drastically and irreversibly [34, 35]. Despite the improvements in visual function, there are frequent risks of ocular complications, such as glaucoma development and progression of pre-existing glaucoma [36, 37]. Hence, vigorous peri-operative management and long-term follow-up are required .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that eyes receiving a primary BKPro achieve better best-corrected visual acuity outcomes when compared with eyes implanted with BKPro after multiple graft failure. 18,24,25 Retention rates of BKPro devices were not statistically significant in primary and secondary implantation.…”
Section: Design Development: Evolution Of the Boston Kpro Typementioning
confidence: 89%
“…The device anatomical-retention rate of 88.9%, found at the mean follow-up time of 83.4 months, was comparable to the reported international long-term results of 79%-89.2%. 8,13,25,26 Apart from the anatomical aspects, the effectiveness of vision can be evaluated by the ability to perform visual orientation. 29 Therefore, meticulous patient selection for surgery is recommended to achieve the most favorable visual function.…”
Section: Discussionmentioning
confidence: 99%
“…6,[19][20][21] As to previous studies on KPro anatomical retention and complications, 7,14,[22][23][24] few have described the long-term outcomes. 8,13,25,26 There is also limited data on whether topical antimicrobial regimens can prevent KPro infections, including fungal infections, especially in high-prevalence areas. The current study therefore set out to describe the long-term visual outcomes and anatomical retention of Boston type I KPro, the risk factors for the outcomes, and the efficacies of prophylactic antimicrobial regimens.…”
Section: Introductionmentioning
confidence: 99%